Tablets Added Combination Blood Vitamin C Affects The Increase of Hemoglobin Levels in Pregnant Women in The Work Area of Karang Anyar Health Center, Beringin Sub-district, Deli Serdang District - Siregar, Yusniar; Linda, Irma; Lubis, Rismahara (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Anemia in pregnant women has a negative impact on both the mother and the fetus, some of which may occur: in the first trimester (abortion, missed abortion and congenital abnormalities), in the second trimester (antepartum bleeding, premature birth, fetus births with anemia, low birth weight, high-birth delivery, high fatigue), when inpartu (primary and secondary disruption, fatigue, high activity delivery), postpartum (difficult to heal, easy puerperalis febris, uterine involution disturbance, death high mothers resulting from bleeding and puerperal infection). This study aimed to determine the effectiveness of giving tablets added blood combination of vitamin B6 and tablets added blood vitamin C combination to increase hemoglobin levels in pregnant women at Karang Anyar health center, Beringin Sub-district, Deli Serdang District in 2015. This study was a quasy experiment research with pretest postest control group design. In this study used two groups of treatment, namely: group A tablet supplementation combined blood vitamin B6, group B administration of tablets plus blood combination of vitamin C. Samples in this study were 62 trimester pregnant women as many as 62 people divided into 2 groups. Data analysis using t-test. There was a difference of hemoglobin group A with group B with p value 0.273> 0.05 and 0.007 <0.005. Given a significant difference between group A and group B then all pregnant women in consuming tablets plus blood should be accompanied by consumption of vitamin C to help the absorption of iron optimally.